Concentration–response relationships of dolutegravir and efavirenz with weight change after starting antiretroviral therapy. Issue 3 (26th January 2022) - Griesel, Rulan; Kawuma, Aida N.; Wasmann, Roeland; Sokhela, Simiso; Akpomiemie, Godspower; Venter, W. D. Francois; Wiesner, Lubbe; Denti, Paolo; Sinxadi, Phumla; Maartens, Gary
Abstract : Dolutegravir is associated with more weight gain than efavirenz in people starting antiretroviral therapy (ART). We investigated the concentration–response relationships of efavirenz and dolutegravir with weight gain. We determined concentration–response relationships of dolutegravir and efavirenz (both combined with tenofovir disoproxil fumarate and emtricitabine) with changes in weight and fat distribution, derived from dual‐energy x‐ray absorptiometry scans, in a nested study of ART‐naïve participants from a randomised controlled trial. Pharmacokinetic parameters used in analyses were efavirenz mid‐dosing interval concentrations and estimated dolutegravir area under the concentration–time curve using a population pharmacokinetic model developed in the study population. Study outcomes were percentage changes from baseline to week 48 in weight, and visceral and subcutaneous adipose tissue mass. Pharmacokinetic data were available for 158 and 233 participants in the efavirenz arm and dolutegravir arms respectively; 57.0% were women. On multivariable linear regression there were independent negative associations between efavirenz concentrations and changes in both weight ( P <  .001) and subcutaneous adipose tissue mass ( P =  .002). Estimated dolutegravir area under the concentration–time curve up to 24 hours was not associated with change in weight ( P =  .109) but was negatively associated with change in visceral adipose tissue mass ( P =  .025). We found an independent negative concentration–response relationship between efavirenz concentrations and weight change in ART‐naïve participants. Dolutegravir concentrations were not independently associated with weight change. These findings suggest that weight gain differences between efavirenz and dolutegravir are driven by efavirenz toxicity impairing weight gain rather than by off‐target effects of dolutegravir causing weight gain.